Analisis Kualitas Pembelajaran Guru Matematika dengan Menggunakan Model EKOP di SMK Teknologi Tri Tunggal 45 Makassar - Sumardin Raupu (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This research is a descriptive study that aimed to describe the quality of learning mathematics teacher at SMK Technology Tri Tunggal "45" based on the Model EKOP Makassar. Model EKOP is one Evaluation Model Learning Program, which not only assess the results (outputs) of learning, but also assesses the learning process carried out by the teacher. The instrument used in this study was a questionnaire given to teachers and students in mathematics teaching by the math teacher. The subjects were all teachers of mathematics in Technological Trinity "45". Analysis of the data used is the average of each component looks for good learning process and learning output, then compares to the quality standards that have been set. The results showed that (1) the quality of the learning process of mathematics teachers in the name of AMRN measured using Model EKOP is Good. (2) The quality of the learning process of mathematics teachers in the name JMT measured using Model EKOP is Good. (3) The output quality of learning mathematics teacher on behalf AMRN measured using Model EKOP is Good. (4) The output quality of learning mathematics teacher on behalf of JMT measured using Model EKOP is Moderate. (5) The quality of mathematics teacher learning program on behalf AMRN measured using Model EKOP are Good. (6) The quality of the learning program for mathematics teachers in the name JMT measured using Model EKOP is Moderate